(untitled) (World Bulletin of Management and Law, 2022)
The article highlights the history and development trend of theoretical of application of legal techniques in different periods – the old, the middle ages, a new period and the latest period. Special attention is paid to the work of scientists who have made a significant contribution to the development of legal techniques in the years of independence and improvement of lawmaking.